2020
DOI: 10.3390/ijms21207496
|View full text |Cite
|
Sign up to set email alerts
|

Toward Drug-Like Multispecific Antibodies by Design

Abstract: The success of antibody therapeutics is strongly influenced by their multifunctional nature that couples antigen recognition mediated by their variable regions with effector functions and half-life extension mediated by a subset of their constant regions. Nevertheless, the monospecific IgG format is not optimal for many therapeutic applications, and this has led to the design of a vast number of unique multispecific antibody formats that enable targeting of multiple antigens or multiple epitopes on the same an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 260 publications
(360 reference statements)
0
51
0
1
Order By: Relevance
“…Multi-specific antibody therapeutics are at high risk for chemical or physical stability issues, 6 , 8 which are difficult to predict from the primary amino acid sequence alone. 7 Usually, such issues become apparent at late discovery stages during comprehensive developability assessments of the drug pre-candidates. To mitigate the risk of late-stage failure, it is therefore desirable to select variants for developability assessments from large variant panels that comprise significant diversity on the sequence or structural level.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-specific antibody therapeutics are at high risk for chemical or physical stability issues, 6 , 8 which are difficult to predict from the primary amino acid sequence alone. 7 Usually, such issues become apparent at late discovery stages during comprehensive developability assessments of the drug pre-candidates. To mitigate the risk of late-stage failure, it is therefore desirable to select variants for developability assessments from large variant panels that comprise significant diversity on the sequence or structural level.…”
Section: Discussionmentioning
confidence: 99%
“…The complex structures of multispecific molecules also present significant challenges in achieving their drug-like properties [32], including favorable physical and chemical stability, solubility, viscosity, polyspecificity, immunogenicity, and pharmacokinetic properties. Compared to conventional monospecific antibody, much less is known about the developability properties of multispecific biotherapeutics.…”
Section: Challenges and Future Directionmentioning
confidence: 99%
“…The topic of multispecific biotherapeutics represents a fast-growing field regarding formats, design strategies, and applications. A number of outstanding review articles have been written on this topic or related themes for the past few years [2][3][4][5][6][9][10][11][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This review summarizes comprehensively the recent advances in molecular design and applications of the multispecific biotherapeutics from the early stages of research discovery to the late stages of clinical and regulatory development.…”
Section: Introductionmentioning
confidence: 99%
“…Both diabodies and tandem scFvs can have two different binding specificities, and in this case, they are called bispecific (bs). Interestingly, even the VH and VL arrangement in the scFv fusion protein can influence the binding activity, and it is currently possible to predict the best functional structure so as to design scFvs that meet all requirements by molecular modelling using a computer-aided homology method [6,7]. A few decades ago, it was observed that the N-terminal IgG fragment including the VH and VL retains the same antigen-binding capacity as the whole IgG molecule.…”
Section: Different Antibody Formats: Mabs Scfvs and Nanobodiesmentioning
confidence: 99%